The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1980
DOI: 10.1002/j.1552-4604.1980.tb01701.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Analgesic Properties of Zomepirac

Abstract: Zomepirac, an inhibitor of prostaglandin biosynthesis, was evaluated for analgesic activity in a number of pharmacological screens. In the acetylcholine writhing test, zomepirac was found to be more potent than codeine, pentazocine, aspirin, and acetaminophen and equivalent in potency to morphine. Zomepirac was inactive in a number of tests that detect narcotic agents, suggesting that the drug will not induce physical dependence. The possibility of a central nonnarcotic as well as a peripheral analgesic mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1980
1980
1990
1990

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The high doses required in this test also produced behavioural side effects which may have indirectly interfered with the animals ability to writhe, in addition to exerting a specific antinociceptive action. Since the doses required to inhibit zymosan-induced writhing were higher than those reported for paracetamol in most animal models of inflammatory pain (Vinegar et al, 1976;Winter et al, 1979;Pruss et al, 1980;Foote et al, 1988), it seems possible that there is some aspect of this model that makes it particularly unresponsive to paracetamol. The doses of paracetamol which inhibited writhing also reduced the synthesis of PGI2, as indicated by the reduced levels of immunoreactive 6-keto-PGF1,.…”
Section: Discussionmentioning
confidence: 91%
“…The high doses required in this test also produced behavioural side effects which may have indirectly interfered with the animals ability to writhe, in addition to exerting a specific antinociceptive action. Since the doses required to inhibit zymosan-induced writhing were higher than those reported for paracetamol in most animal models of inflammatory pain (Vinegar et al, 1976;Winter et al, 1979;Pruss et al, 1980;Foote et al, 1988), it seems possible that there is some aspect of this model that makes it particularly unresponsive to paracetamol. The doses of paracetamol which inhibited writhing also reduced the synthesis of PGI2, as indicated by the reduced levels of immunoreactive 6-keto-PGF1,.…”
Section: Discussionmentioning
confidence: 91%
“…8,9 In addition, zomepirac does not carry the risk of drug tolerance or addiction, and is lacking in withdrawal symptoms even after extended use. [9][10][11][12] Overall, this study indicates that zomepirac is an effective and well-tolerated analgesic for the symptomatic treatment of patients with muscle-contraction headache who require a prescription analgesic.…”
Section: Resultsmentioning
confidence: 97%
“…Our analysis of literature ED50 values for the mouse ACh-assay has shown that it is certainly valid to routinely use this test as a primary screen in a battery of antialgesic assays. Table 7 shows an equation derived by stepwise multiple regression analysis which predicts the clinical dose from laboratory Pharmacologic research in the laboratory [51] and clinic [52,53] has brought about significant advances in antialgesic specificity and has produced drugs with, in certain instances, analgesic activity as efficacious as morphine, Thus, zomepirac is as active (efficacious) as morphine in cancer pain [52,53]. Pain may be acute and due to trauma, headache, dental decay, menstruation, postoperative sequale, trigeminal neuralgia or surgery.…”
Section: Discussionmentioning
confidence: 99%